Anatomical and ultrastructural analysis of the posterior optic tubercle in the locust Schistocerca gregaria. (September 2020) - Held, Martina; Le, Kim; Pegel, Uta; Dersch, Florian; Beetz, M. Jerome; Pfeiffer, Keram; Homberg, Uwe
Abstract: Locusts, like other insects, partly rely on a sun compass mechanism for spatial orientation during seasonal migrations. To serve as a useful guiding cue throughout the day, however, the sun's apparent movement has to be accounted for. In locusts, a neural pathway from the accessory medulla, the circadian pacemaker, via the posterior optic tubercle, to the protocerebral bridge, part of the internal sky compass, has been proposed to mediate the required time compensation. Toward a better understanding of neural connectivities within the posterior optic tubercle, we investigated this neuropil using light and electron microscopy. Based on vesicle content, four types of synaptic profile were distinguished within the posterior optic tubercle. Immunogold labeling showed that pigment-dispersing hormone immunoreactive neurons from the accessory medulla, containing large dense-core vesicles, have presynaptic terminals in the posterior optic tubercle. Ultrastructural examination of two Neurobiotin-injected tangential neurons of the protocerebral bridge revealed that these neurons are postsynaptic in the posterior optic tubercle. Our data, therefore, support a role of the posterior optic tubercles in mediating circadian input to the insect sky compass. Graphical abstract: Image 1 Highlights: We analyzed the ultrastructure of the posterior optic tubercle in the locust brain. Four types of synaptic profile were distinguished in the tubercle. PDF-neurons from the accessory medulla were presynaptic in the tubercle. Tangential neurons of the protocerebral bridge were postsynaptic in the tubercle. Data support a role of the tubercle in time compensation of the locust sky compass.